THE PERSISTENCE SPATIAL SETTLEMENTS BALUWARTI SURAKARTA SINCE 1749-2018 (DIMENSI: Journal of Architecture and Built Environment, 2019)
The background of Baluwarti settlement establishment derived from formal bond between people (kawula) and the court. This formal bond can be status of abdi dalem (giving service to the king/court) with title or kekancingan from the King. Dwelling was classified by status, role, and grade of respective dwellers. Thus, Baluwarti settlement is believed to have typical spatial layout because it was constructed with the Court’s traditional and cultural value concepts remaining to be visible today. Based on qualitative research paradigm and historical reading method, this research could see that the spatial layout of Baluwarti Settlement is circling or going around kedhaton concentrically. Single orientation faces to kedhaton . This form has a spatial function as defense and security system, serving or subjugating system, and tradition preserving system. Overall, the original form of Baluwarti Settlement’s spatial layout is still maintained until today, for about 270 years.